The 'First' Metric: The 'WE' Index, Responsiveness, and Cultural Scripts - Hikmanisa Bahtiar; Muhammad Kholdinna Qasabandiyah (Research and Innovation in Social Science Education Journal (RISSEJ), 2025)
"First love" is often understood as the earliest romantic relationship, but evidence from psycholinguistics, interpersonal communication, and autobiographical memory suggests that it is more accurately conceptualized as a narrative cognitive status. This article presents a structured narrative review and introduces a minimal measurement framework for assessing this status through three indicators: the WE Index, defined as the proportion of “we/us” pronouns relative to personal pronouns and love labels or metaphors; Perceived Responsiveness; and Age Event Compatibility as a proxy for cultural scripts. Drawing on a synthesis of more than 100 peer reviewed studies, the article proposes a process model linking WE Index to Responsiveness, Event Centrality, and First Love Labeling, with emotional intensity and age event fit acting as contextual drivers or moderators. The synthesis reveals consistent patterns: a higher WE Index is associated with higher perceived responsiveness; responsiveness facilitates shared reminiscing and increases event centrality; and higher centrality predicts the labeling of an experience as “first love,” particularly when age event expectations are culturally congruent. The article also outlines a rapid operationalization package, including a 5 to 10 minute speech sample, a brief responsiveness scale, a short age event fit check, and a concise centrality measure, designed for replication in small scale research and educational contexts. As a narrative review, this framework does not estimate effect sizes and is subject to heterogeneity and retrospective bias across included studies, indicating the need for future empirical testing.